Current Diagnostic and Therapeutic Aspects of Eosinophilic Myocarditis. (17th January 2016) - Kuchynka, Petr; Palecek, Tomas; Masek, Martin; Cerny, Vladimir; Lambert, Lukas; Vitkova, Ivana; Linhart, Ales
Abstract : Eosinophilic myocarditis (EM) represents a rare form of myocardial inflammation with very heterogeneous aetiology. In developed countries, the most prevalent causes of EM are hypersensitivity or allergic reactions, as well as hematological diseases leading to eosinophilia. The disease may have a variable clinical presentation, ranging from asymptomatic forms to life-threatening conditions. Most patients with EM have marked eosinophilia in peripheral blood. Endomyocardial biopsy needs to be performed in most cases in order to establish a definitive diagnosis of EM. The therapy depends on the underlying aetiology. Immunosuppressive therapy represents the treatment mainstay in the majority of EM forms.